Effectiveness of educational electronic games to the mathematical skills of the kindergarten pupils - Florence Ileona Canastra Fernandez; Beatriz Andrea Rallos Gorayeb; Andrea ae Marjes Masa and Shane Fedelicio Romano. 4 0 16; 5 (2016)
ABSTRACT: The purpose of the study was to determine the effectiveness of educational electronic games to the mathematical skills of the kindergarten pupil at Teodoro Rafael Yangco Elementary School. To gather and result of the study, the researchers made a 15 item test (pre-test and post-test) that was validated by three experts in the field of education with their specific specializations. This study used the quasi experimentation wherein 22 students are chosen by simple random sampling. In addition, to know the significant difference the researchers used t-test as the statistical treatment. The result showed that the educational electronic games is effective in enhancing the kindergarten pupils mathematical skills that is why the researchers come up with an idea to create a module that contains lesson on how teachers can do their own games and other tools to use that may help them to make teaching fun and exciting.
Thesis: (Bachelor of Elementary Education with Specialization in Preschool Education) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2